Castle and crisis in Ashwin Sanghi`s The Krishna Key - Pathinathan, Santini; Mani, Manimangai (Center for Resource, Research and Publication Services (CRRPS) India, 2017)
This study looks into the features of time and space in a postmodern Indian English novel. It is crucial to understand the meaning of temporal and spatial indicators and references in order to understand a narration. This study aims to explore the portrayal of chronotope in the chosen novel. Bakhtin’s literary theory of Chronotope is chosen for this study because it is yet to be used to analyse an Indian English suspense thriller novels. Most studies that applied Bakhtin’s literary theory of Chronotope are modern literary works. To date, there are very few studies that have applied this theory on postmodern literary works and even fewer that have used it to analyse Asian literary works what more suspense thrillers. This study has picked out a few of the time-space indicators from the novel The Krishna Key by Ashwin Sanghi in order to explore them according to Bakhtin’s literary theory of Chronotope as he discussed in his essay Forms of Time and Chronotope in the Novel in his essay collections, The Dialogic Imagination. The concepts discussed in this study are the chronotope of the castle and crisis / threshold.